2020
DOI: 10.4103/apjon.apjon_22_19
|View full text |Cite
|
Sign up to set email alerts
|

Does Being A Cancer Patient or Family Caregiver of A Cancer Patient Affect Stem Cell Donation Awareness?

Abstract: Objective:One of the most difficult challenges regarding hematopoietic stem cell transplantation in Turkey is finding donors for allogeneic transplantation candidates who do not have related donors. This study aims to determine whether there is any difference in the awareness of stem cell donation and transplantation between cancer and noncancer patients and their family caregivers. In addition, this study aims to determine the awareness of stem cell donation and transplantation in the entire study population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It was observed that people with a relative in need of transplantation or a family history of blood cancer/organ cancer were more willing to donate hematopoietic stem cells and organs (Koçak et al, 2010;Studts et al, 2010;Ozturk Emiral et al, 2017;Kulakcı Altıntaş, 2018;Bagcivan et al, 2020). The results of our study are in line with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…It was observed that people with a relative in need of transplantation or a family history of blood cancer/organ cancer were more willing to donate hematopoietic stem cells and organs (Koçak et al, 2010;Studts et al, 2010;Ozturk Emiral et al, 2017;Kulakcı Altıntaş, 2018;Bagcivan et al, 2020). The results of our study are in line with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…There have been studies in Turkey assessing the knowledge of medical faculty students (15) and the knowledge of cancer patients or people having cancer patients in their families (16) regarding being bone marrow transplantation donors. However, we have not come across any study in the literature assessing the knowledge level of people regarding being bone marrow donors involving all hospital employees.…”
Section: 2% Of Them (40 People)mentioning
confidence: 99%
“…However, few studies have been carried out with caregivers of HSCT patients, and these studies have been mostly quantitative. 19,20 There have been a few qualitative studies and these studies have not reflected the perceptions, thoughts and feelings of ICs at BMT units. [21][22][23] Therefore, in this study, it was aimed to investigate the perceptions of ICs of HSCT patients at a BMT unit in Türkiye in depth.…”
mentioning
confidence: 99%